Stakeholder informed non-traditional student induction: a balanced approach - Soontiens, Werner; Kerr, Rosie; Ang, Grace; Scully, Glennda (Emerald Group Publishing Ltd., 2016)
The purpose of this paper is to consider the evolution of a tailored university induction program over time to establish the change in the nature and content of the program. Design/methodology/approach – The induction program is pitched against the conceptual backdrop of academic norms and conventions, language, integration and the role of mentoring. As an exploratory study of a unique and complex induction program it reports on the basis of discourse analysis over time (from 2009 to 2012). Findings – The paper establishes that consideration of feedback by students, university staff (academic and professional) and external stakeholders has allowed the program to morph to a balanced content of academic; social; and socio-academic integration activities. Research limitations/implications – The paper confirms the framework proposed by Zepke and Leach (2005) and renders a further level of validity to the model when applied in a cross-cultural higher education context. Practical implications – Practical implications include the value of involving stakeholders as source of knowledge for considering continuous improvements and the notion that a remedial approach to integration of international students proves to be ineffective. Originality/value – Articulation pathways for Chinese university students into Australian universities create a unique set of expectations and challenges to both the students and the Australian universities. A tailor made induction program is a crucial step in addressing these and requires continuous improvement to retain relevance and optimize impact and resources.